Interdisciplinarity, E-Mentoring and Support of Entrepreneurial Research Skills - Hamburg, Ileana (Advances in Social Sciences Research Journal, 2020)
Innovation requires the development of entrepreneurial skills in order to provide a new approach to the work and solutions to a challenge in the corresponding enterprise. Research skills can help entrepreneurs throughout your career i.e. to develop an innovative project, to find an answer to a question. to find data and information about a topic, analyze and interpret this information to find a solution. Mentoring is understood mostly as a supportive relationship to guide the successful integration of new members/entrepreneurs into an organization or to help entrepreneurs to be innovative and add value to the organization. E-mentoring helps a mentee to obtain knowledge with the support of a mentor who is physically not present but using digital technologies. One important conceptual change regarding mentoring in both business and education is the emphasis on the need for more than a single mentor i.e. networks of mentors who may provide both technical careers advancing advice and psychosocial support. Interdisciplinary mentorship is a tool of scientists and entrepreneurs to help produce synergy in groups, and to generate multifocal ideas and complex solutions to complex challenges. This paper examines entrepreneurial learning, mentoring and entrepreneurial research skills as main factors for development of innovation in companies. An example of a project in the context of achieving workplace-oriented research skills of entrepreneurs is given. A part of the project runs within the Coronavirus crisis, so entrepreneurs learn and interact mainly by using a digital platforms and E-mentors.